THE ROLE OF CELEBRITY ENDORSEMENT, CONTENT MARKETING, AND PRODUCT QUALITY ON PURCHASING DECISIONS OF ULTRA MILK BRAND UHT MILK PRODUCTS - Yunia Najachatul Chusnah; Lilik Indayani; Kumara Adji Kusuma; Rizky Eka Febriansah (Journal of Artificial Intelligence and Digital Economy, 2025)
Objective: This study aims to analyze the influence of Celebrity Endorsement, Content Marketing, and Product Quality on Purchasing Decisions for Ultra Milk brand UHT milk products in Sidoarjo. Method: The research adopts a quantitative approach with a population consisting of consumers residing in Sidoarjo who have purchased Ultra Milk products. A total of 100 respondents were selected using the purposive sampling technique, and data were collected through a structured questionnaire. The data analysis was performed using IBM SPSS Statistics Version 26 for Windows to test the effect of each independent variable on purchasing decisions. Results: The findings reveal that Celebrity Endorsement has a negative and insignificant impact on Purchasing Decisions, while both Content Marketing and Product Quality have positive and significant effects. Novelty: This study provides a contemporary perspective on consumer purchasing behavior in the dairy industry by integrating digital marketing variables with traditional marketing elements, offering valuable insights for companies seeking to optimize marketing strategies in competitive fast-moving consumer goods (FMCG) markets.